Virulence profile of carbapenem-resistant Klebsiella pneumoniae strains by an in vivo model of Galleria mellonella - María Guembe; Rama Hafian; Marta Díaz-Navarro; Andrés Visedo; Flavio De Maio; Fulvia Pimpinelli; Ilaria Cavallo; Mauro Truglio; Francesca Sivori; Enea Gino Di Domenico (Microbiology Spectrum)
ABSTRACT Klebsiella pneumoniae is a significant healthcare-associated pathogen, notable for its diverse virulence and antibiotic resistance profiles. This study aimed to characterize the genotypic and phenotypic diversity of K. pneumoniae isolates and evaluate their virulence using the Galleria mellonella model. Biomass production, metabolic activity, capsule formation, and siderophore production were assessed in 27 K. pneumoniae isolates from hospital-associated infections. Lethality curves were generated using the G. mellonella model, with survival monitored hourly from 16 to 48 hours. The most common sequence types (ST) identified were the high-risk clones ST307 (N = 10), ST512 (N = 8), ST101 (N = 7), and ST661 (N = 2). These STs were associated with distinct K-locus, including KL102, KL107, KL17, and KL39. Most isolates belonged to the O2afg locus (N = 18), with the K. pneumoniae carbapenemase genotype detected in 96.3% of strains. None of the isolates were classified as hypervirulent. Phenotypically, ST661 exhibited the highest biomass production despite showing similar metabolic activity to other STs. A positive correlation was observed between biomass and siderophore production, while capsule production was inversely correlated with biomass. In the G. mellonella model, ST661 demonstrated the highest virulence, resulting in 100% mortality by 48 hours, compared to survival rates of 21.4% for ST101, 38.0% for ST307, and 31.2% for ST512. These findings underscore the pathogenic potential of ST661 isolates with enhanced biofilm production. The G. mellonella model may serve as an effective in vivo system for evaluating the virulence of emerging K. pneumoniae lineages.IMPORTANCEWe demonstrate that the Galleria mellonella model is a useful tool to analyze the virulence of carbapenem-resistant Klebsiella pneumoniae strains. Our findings highlight the pathogenicity of carbapenem-resistant K pneumoniae isolates, particularly the role of the ST661 that, despite being a rare lineage, harbors the blaVIM gene and is associated with high biofilm production and the highest mortality rates.